2015
DOI: 10.1590/0004-282x20140223
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control study of the prevalence of neurological diseases in inflammatory bowel disease (IBD)

Abstract: Neurological diseases are common in inflammatory bowel disease (IBD) patients, but their exact prevalence is unknown. Method: We prospectively evaluated the presence of neurological disorders in 121 patients with IBD [51 with Crohn's disease (CD) and 70 with ulcerative colitis (UC)] and 50 controls (gastritis and dyspepsia) over 3 years. Results: Our standard neurological evaluation (that included electrodiagnostic testing) revealed that CD patients were 7.4 times more likely to develop large-fiber neuropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…In other patients, it may occur in the context of systemic autoimmune disease [3,4], and autonomic neuropathy may be the initial manifestation of Sjogren syndrome [5] or the antiphospholipid syndrome [6], which may coexist. Dysautonomia may also occur in association with most other autoimmune diseases, including some cases of Hashimoto thyroiditis [4], rheumatoid arthritis, [7] spondyloarthropathy [8], lupus [9], systemic sclerosis [10], celiac disease [11], inflammatory bowel disease [12], myasthenia gravis [13], and multiple sclerosis [1]. Indeed, it has been hypothesized that autonomic dysregulation may be involved in the etiopathogenesis of systemic autoimmunity as a result of the complex interactions between the immune system and the autonomic nervous system [14].…”
Section: Introductionmentioning
confidence: 99%
“…In other patients, it may occur in the context of systemic autoimmune disease [3,4], and autonomic neuropathy may be the initial manifestation of Sjogren syndrome [5] or the antiphospholipid syndrome [6], which may coexist. Dysautonomia may also occur in association with most other autoimmune diseases, including some cases of Hashimoto thyroiditis [4], rheumatoid arthritis, [7] spondyloarthropathy [8], lupus [9], systemic sclerosis [10], celiac disease [11], inflammatory bowel disease [12], myasthenia gravis [13], and multiple sclerosis [1]. Indeed, it has been hypothesized that autonomic dysregulation may be involved in the etiopathogenesis of systemic autoimmunity as a result of the complex interactions between the immune system and the autonomic nervous system [14].…”
Section: Introductionmentioning
confidence: 99%
“…This may be true in children, although supportive prospective data are lacking. However, we and others have reported that neurological diseases are not uncommon in adult IBD, including with a recently published prospective study [2][3][4]. Second, they state that MG is rare in IBD, yet that MG appears to be more common in IBD than in the normal population [5].…”
Section: Déclaration D'intérêtsmentioning
confidence: 68%
“…Les produits de substitutions représentent la deuxième cause d'intoxication par ingestion, après les cigarettes, et leur proportion augmente entre 0 et 5 ans [1]. L'American Association of Poison Control Centers (AAPCC) [2] a recensé en 1995 près de 8000 cas d'intoxication dus aux produits tabagiques chez les enfants âgés de moins de 6 ans aux États-Unis, la plupart par ingestion de cigarettes. La sévérité des symptômes est corrélée à la quantité absorbée.…”
unclassified
“…Twenty percent of IBD patients showed large-fiber neuropathy; and twelve percent of CD and UC patients showed SFN demonstrated by skin wrinkling test and quantitative sensory testing. PN was the most common neurologic condition reported although the relation between the PN and vitamin B12 levels or the presence of diabetes mellitus and glucose intolerance were not addressed [36,37]. Patients with UC and CD were enrolled as control group in a study undertaken to know the prevalence of PN in patients with celiac disease in a US population.…”
Section: Frequency Of Ibd-associated Peripheral Neuropathiesmentioning
confidence: 99%